Pertanggung Jawaban Hukum bagi Pelaku Cyberbullying yang Menjadi Korban Penyebaran Data Pribadi - Sheyla Dhea Permatasari; Rosalinda Elsina Latumahina (Lembaga Pengembangan Kinerja Dosen, 2024)
In the current era of modern technology and through the development of digital information technology (IT), which is growing very rapidly and provides many conveniences for everyone to own and access various things in cyberspace, especially on the internet, and can be accessed quickly with a finger. just seconds to be able to display and get the information we need and we can find out via the internet. This is in line with the rapid development of information technology which makes it easier to obtain information and makes it increasingly difficult for us to escape from the convenience of technology which makes human life easier. Every developmental innovation is expected to be able to provide positive benefits for human life in the technological progress which has greatly developed in the technological era. creating many conveniences for accessing things in information systems. It can be concluded that the progress of the virtual world (internet) has changed the times without limiting computer network providers which contain many different systems. And all information activities can be accessed easily via social media, and this is what makes people dependent on technology as a daily necessity to increase convenience and obtain information quickly